Lanthanide modification strategy with double effects of surface coating and interlayer doping

By adopting the lanthanide modification strategy on the positive electrode material of lithium-ion batteries, the lanthanide oxide coating and cognano precipitation phase are formed, and the structural instability of the positive electrode material is solved, which significantly improves the cycle stability and electrochemical performance. .

CN119400822AActive Publication Date: 2025-02-07WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411487752.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The structural instability of the cathode material of lithium-ion batteries during long-term circulation leads to a reduced cycle life, especially the problem of surface oxygen loss seriously affects the electrochemical performance.

Method used

Using the lanthanide modification strategy, a Q1-x-yMxNyO1.9 lanthanide oxide coating layer with oxygen-rich vacancies was formed on the surface of the positive electrode material, and a co-catenated nanoprecipitation phase was formed between the material layers to achieve surface coating and layer The dual modification effect of inter-class doping.

Benefits of technology

It significantly improves the cyclic stability of the material, effectively suppresses the voltage drop, enhances the structural stability, and thus improves the overall electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400822A_ABST
    Figure CN119400822A_ABST
Patent Text Reader

Abstract

The invention aims to develop a lanthanide series modification strategy with wide application potential, the strategy can form a Q < 1-x-y > M < x > N < y > O < 1.9 > lanthanide series oxide coating layer rich in oxygen vacancies on the surface of the lithium ion battery positive collection material, and a coherent nano precipitated phase is formed between material layers, so that the dual modification effects of surface coating and interlayer doping are realized. Benefited from the double modification, the cycling stability of the material is obviously improved, the voltage drop is effectively inhibited, and the structural stability is obviously enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials and electrochemistry, and in particular relates to a modification strategy with dual effects of surface coating and interlayer quasi-doping. Background Art

[0002] Lithium-ion batteries have achieved remarkable application achievements in the fields of communications and consumer electronics, and have gradually expanded to the fields of electric vehicles and renewable energy storage. Faced with the growing demand for high energy density, the research on new high-capacity electrode materials, especially Zhengji materials, has become the focus of scientific research. However, the structural instability of positive electrode materials in long-term cycles seriously affects their cycle life. Therefore, achieving the structural stability of materials is crucial to improving their electrochemical performance.

[0003] Taking lithium-rich manganese-based cathode materials (LLOs) as an example, their reversible capacity of more than 250 mAh·g−1 makes them potential candidate materials to meet the needs of high energy density. Studies have shown that the high capacity of LLOs not only comes from cation redox reactions, but also involves anion redox reactions. These anion redox reactions are mainly manifested as bulk reversible anodic redox and surface irreversible oxygen loss. Surface oxygen loss will reduce the electrochemical performance of LLOs, trigger electrolyte decomposition and structural reconstruction, leading to the formation of non-conductive SEI film, and then induce a phase transition from layered structure to spinel structure, hindering the diffusion of lithium ions, thereby causing capacity decline, voltage decay and kinetic performance deterioration. Previous atomic structure and chemical observations have pointed out that the phase transition in LLOs starts from the surface and gradually extends to the inside during the cycle process. Therefore, achieving structural stability of LLOs materials, especially surface stability to mitigate the release of lattice oxygen, is of vital importance for the development of better cathode materials and promoting the development of next-generation lithium-ion batteries.

[0004] In order to achieve the structural stability of positive electrode materials, various modification strategies have been widely studied and applied, including doping, coating, and structural design. Although the traditional method of surface coating of battery positive electrode materials can improve the cycle stability and durability of the materials to a certain extent, it often has problems such as uneven coating thickness, increased interface impedance, and easy peeling of the coating layer. In addition, traditional coating methods are difficult to optimize the overall performance of the material and can only provide limited protection on the surface. Therefore, combining various modification strategies and developing new modification methods to improve the structural stability of positive electrode materials and thereby improve the electrochemical properties of the materials such as cycle life has become an important direction of current research. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to develop a lanthanide modification strategy with wide application potential, which can form Q-rich oxygen vacancies on the surface of the positive electrode material.1-x-y M x N y O 1.9 A lanthanide oxide coating layer, where 0 < x < 1, 0 < y < 1, Q, M, and N are a composition of one or more of La, Ce, Pr, Nd, Pm, Sm, Sc, Y, and Yb, and a coherent nano-precipitation phase is formed between the material layers, thereby achieving the dual modification effects of surface coating and interlayer pseudo-doping. Thanks to this dual modification, the cycle stability of the material is significantly improved, the voltage drop is effectively suppressed, and the structural stability is significantly enhanced.

[0006] To achieve the above object, the present invention adopts the following technical solutions: A lanthanide-coated and doped dual-modified cathode composite material, characterized in that a Q rich in oxygen vacancies can be formed on the surface of the cathode material of the lithium-ion battery 1-x-y M x N y O 1.9 A lanthanide oxide coating layer, where 0 < x < 1, 0 < y < 1, Q, M, and N are a composition of one or more of La, Ce, Pr, Nd, Pm, Sm, Sc, Y, and Yb. The lanthanide elements in the oxygen vacancy lanthanide oxide coating layer are doped into the layered structure of the cathode material, and a coherent nano-precipitation phase is formed between the material layers to achieve the dual modification of surface coating and interlayer pseudo-doping.

[0007] Further, in the lanthanide-coated and doped dual-modified cathode composite material, Q is Ce, M is La, and N is Yb.

[0008] Further, in the lanthanide-coated and doped dual-modified cathode composite material, 0 < x < 0.35 and 0 < y < 0.35.

[0009] Further, a Q rich in oxygen vacancies is formed on the surface 1-x-y M x N y O 1.9 The stoichiometric ratio of each lanthanide element in the lanthanide oxide is 1:1:1, and the thickness of the coating layer is 1 - 5 nm. If the thickness of the coating layer is too thin, the coating effect of the coating layer cannot be fully presented. If the thickness of the coating layer is too thick, it will affect the entry of ions and electrons into the active material and affect the electrochemical performance of the material. Therefore, it is preferably within this range, which can ensure both the strength and effect of the coating layer and also take into account the electrochemical performance.

[0010] On the other hand, the present invention also provides a preparation method of the lanthanide-coated and doped dual-modified cathode composite material, characterized by including the following steps: 1) Dissolve different lanthanide element sources in a certain amount of N,N-dimethylformamide (DMF) according to the stoichiometric ratio to form a uniform solution; 2) A certain mass of original cathode material powder is dissolved in a certain amount of the above solution, placed in a vacuum environment and mixed evenly, and then the mixed product is washed multiple times with DMF solution; 3) Drying the product obtained in the previous step in a vacuum oven, and then sintering the dried product to obtain a modified positive electrode composite material.

[0011] Furthermore, in the step 1), the lanthanide source in the step 1) is one or more of nitrates, acetates, sulfates and chlorides of lanthanide.

[0012] Furthermore, in step 2), the concentration of the final mixed solution is 0.1-1 mol / L.

[0013] Furthermore, in the step 2), the original positive electrode material powder includes primary particles synthesized by the sol-gel method and secondary particles synthesized by the coprecipitation-solid phase method, the stirring temperature is 50-120° C., the time is 5-12 h; and the DMF solution is repeatedly filtered and washed 3 times.

[0014] Furthermore, in step 3), the drying condition is drying at 120-140°C for 12 h in a vacuum oven; the sintering condition is heating to 600-800°C at a heating rate of 5°C / min, keeping the temperature for 6-12 h, and naturally cooling to room temperature.

[0015] The third aspect of the present invention is to provide a lanthanide-coated doped dual-modified positive electrode composite material or the use of the lanthanide-coated doped dual-modified positive electrode composite material prepared by the above method in a battery, wherein the battery includes a lithium ion battery, a sodium ion battery, and a potassium ion battery.

[0016] The beneficial effects of the present invention are: This paper reveals an effective lanthanide modification strategy that can form oxygen vacancy-rich Q on the surface of lithium-ion battery cathode materials. 1-x-y M x N y O 1.9 The lanthanide oxide coating layer forms a coherent nano-precipitated phase between the material layers, thereby achieving the dual modification effects of surface coating and interlayer doping. The lanthanide oxide coating layer with certain oxygen vacancies formed on the surface after lanthanide modification can effectively inhibit the release of lattice oxygen and reduce the occurrence of side reactions. In addition, the precipitated nano-phase produced between the layers has a doping effect, which helps to maintain the stability of the layered structure. The cyclic stability of the material modified by lanthanide is significantly improved, the voltage drop is effectively suppressed, and the structural stability is significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1(a) XRD spectrum and (b) SEM image of the lithium-rich material LLO-L after lanthanide modification in Example 1 and the original lithium-rich material LLO.

[0018] Figure 2 (a) HAADF-STEM image and (b) EDS mapping diagram of the lithium-rich material LLO-L after lanthanide modification in Example 1.

[0019] Figure 3 This is the atomic-level HAADF-STEM image of the lithium-rich material LLO-L after lanthanide modification in Example 1.

[0020] Figure 4 This is a comparison chart of the cycling performance of the lithium-rich material LLO-L after lanthanide modification in Example 1 and the original lithium-rich material LLO at a rate of 0.2 C.

[0021] Figure 5 This is a comparison chart of the cycling performance of the lithium-rich material LLO-L after lanthanide modification in Example 1 and the original lithium-rich material LLO at a 1 C rate.

[0022] Figure 6 This is a high-magnification HAADF-STEM image of the original lithium-rich material in Example 1 after 200 LLO cycles.

[0023] Figure 7 This is a high-magnification HAADF-STEM image of the lithium-rich material LLO-L after lanthanide modification in Example 1.

[0024] Figure 8 This is the SEM image of the original secondary particle cobalt-free lithium-rich material LRNM in Example 2.

[0025] Fig. 9 This is a SEM image of the secondary particle cobalt-free lithium-rich material L-LRNM after lanthanide modification in Example 2.

[0026] Fig.10 This is the HAADF-STEM image of the secondary particle cobalt-free lithium-rich material L-LRNM after lanthanide modification in Example 2.

[0027] Fig.11 This is a comparison chart of the cycling performance of the secondary particle cobalt-free lithium-rich material L-LRNM after lanthanide modification in Example 2 and the original secondary particle cobalt-free lithium-rich material LRNM at a 1 C rate. DETAILED DESCRIPTION

[0028] In order to make the technical solutions and advantages of the present invention clearer, the present invention and its beneficial effects will be further described in detail below in combination with specific implementation methods and the accompanying drawings of the specification, but the implementation methods of the present invention are not limited thereto. In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully below in combination with the accompanying drawings of the specification and preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0030] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0031] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0032] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0033] Embodiment 1: 1) Dissolve 1.737 g of cerium nitrate hexahydrate, 1.732 g of lanthanum nitrate hexahydrate and 1.797 g of ytterbium nitrate pentahydrate in 40 ml of DMF solution and mix thoroughly to form a 0.1 mol / L uniform solution.

[0034] 2) Take 0.2 g of primary lithium-rich material powder (LLO) prepared by the sol-gel method and dissolve it in 4 ml of the above-prepared solution, place it in a vacuum environment, and stir it at 50 °C for 12 h to fully mix. The subsequent product is filtered and washed repeatedly with DMF solution for 3 times.

[0035] 3) The product obtained in the previous step was placed in a vacuum oven at 120 °C and dried for 12 h to remove excess DMF. The dried product was then placed in a muffle furnace and heated to 675 °C at a rate of 5 °C / min, kept at that temperature for 6 h, and naturally cooled to room temperature before being taken out to complete the lanthanide modification (LLO-L).

[0036] Taking the lithium-rich material powder (LLO) of the primary particles of this embodiment as an example, it was subjected to lanthanide modification (LLO-L), which confirmed the effectiveness of this strategy for modifying the primary particle Zhengji material samples.

[0037] Figure 1 The XRD results in the figure show that the lanthanide-modified (LLO-L) sample retains the characteristic peaks of LLO rich lithium, while additional tiny peaks appear at diffraction angles of 30-35° and 47°. Through the magnified image of the (003) peak, it is found that the (003) peak in the LLO-L sample shifts to the low-angle direction, further indicating that the lanthanide elements are successfully doped into the lattice of the material. SEM image analysis shows that the surface structure of LLO particles is relatively clean and smooth, while a clear coating layer is observed on the surface of LLO-L particles, indicating the success of lanthanide coating.

[0038] Figure 2 The HAADF-STEM image and EDS mapping also prove the success of the lanthanide modification strategy.

[0039] pass Figure 3 Atomic-level HAADF-STEM images confirm the presence of obvious Ce on the surface after lanthanide modification 1-x- y La x Yb y O 1.9 Lanthanide oxide coating layer, and form a coherent nano-precipitation phase between material layers.

[0040] Figure 4 This is a comparison of the cycling performance of the lanthanide-modified lithium-rich material LLO-L and the original lithium-rich material LLO at a rate of 0.2 C. After 200 cycles, LLO has only a capacity retention rate of 73.54%, while after lanthanide modification, LLO-L still has a capacity retention rate of 87.75%, showing better cycling stability than LLO.

[0041] Figure 5 The following is a comparison of the cycling performance of the two at a rate of 1 C. After 500 cycles, LLO has only a capacity retention rate of 69.81%, while after lanthanide modification, LLO-L still has a capacity retention rate of 80.39%, showing ultra-high cycling stability.

[0042] Figure 6 This is the structural characterization of the original lithium-rich material LLO after 200 cycles. After the original LLO cycle, a large number of black holes appeared on the surface, accompanied by lattice distortion, and severe phase transition. The lattice oxygen loss was very serious, and the structure was severely damaged, so it showed poor cycle stability.

[0043] Figure 7This is the structural characterization of the lanthanide-modified lithium-rich material LLO-L after 200 cycles. The lanthanide coating and precipitated nanophase in the material still exist after the cycle, and the structure remains intact. In addition, only a small number of holes appear on the surface after the cycle, the degree of adverse phase change on the surface is low, and no obvious lattice distortion is found, and the release of lattice oxygen is well suppressed. The lanthanide oxide coating layer with certain oxygen vacancies formed on the surface after lanthanide modification can effectively inhibit the release of lattice oxygen and reduce the occurrence of side reactions. In addition, the precipitated nanophase produced between the layers has a doping effect, which helps to maintain the stability of the layered structure.

[0044] Embodiment 2: 1) Dissolve 1.737 g of cerium nitrate hexahydrate, 1.732 g of lanthanum nitrate hexahydrate and 1.797 g of ytterbium nitrate pentahydrate in 40 ml of DMF solution and mix thoroughly to form a 0.1 mol / L uniform solution.

[0045] 2) Take 0.2 g of cobalt-free lithium-rich material powder (LRNM) prepared by coprecipitation-solid phase method and dissolve it in 4 ml of the above-prepared solution, place it in a vacuum environment, stir it at 50 °C for 12 h to mix it thoroughly, and then the product is filtered and washed three times with DMF solution.

[0046] 3) The product obtained in the previous step was placed in a vacuum oven at 120 °C and dried for 12 h to remove excess DMF. The dried product was then placed in a muffle furnace and heated to 675 °C at a rate of 5 °C / min, kept at that temperature for 6 h, and naturally cooled to room temperature before being taken out to complete the lanthanide modification (L-LRNM).

[0047] Taking the cobalt-free lithium-rich material powder (LRNM) of the secondary particles of this embodiment as an example, it was subjected to lanthanide modification (L-LRNM), which confirmed the effectiveness of this strategy for modifying the secondary particle positive electrode material samples.

[0048] Figure 8 and Fig. 9 These are the SEM images of the original cobalt-free lithium-rich material powder LRNM and the lanthanide-modified L-LRNM. Both are spherical secondary particles of about 10 μm composed of primary particles of tens of nanometers. After lanthanide modification, there is an obvious coating layer in L-LRNM, and the gaps between the primary particles are filled.

[0049] Fig.10 Atomic-scale HAADF-STEM image of lanthanide-modified L-LRNM. An obvious coating layer was observed on the surface, and a coherent nanoprecipitate phase was formed between the material layers. This confirms the success of the lanthanide modification and the universality of the lanthanide modification strategy in secondary particle materials.

[0050] Fig.11 The figure shows the cycling stability comparison of the original cobalt-free lithium-rich material powder LRNM and the lanthanide-modified L-LRNM at 1 C rate. The original cobalt-free lithium-rich material LRNM has only a 70.96% capacity retention rate after 400 cycles, while the lanthanide-modified L-LRNM still maintains an excess capacity of 93.19%, showing excellent cycling stability.

[0051] Embodiment three: 1) Dissolve 1.737 g of cerium nitrate hexahydrate, 1.732 g of lanthanum nitrate hexahydrate and 1.797 g of ytterbium nitrate pentahydrate in 20 ml of DMF solution and mix thoroughly to form a 0.2 mol / L uniform solution.

[0052] 2) Take 0.2 g of primary single crystal high nickel NCM811 powder and dissolve it in 4 ml of the above prepared solution, place it in a vacuum environment, stir it at 80 °C for 10 h to fully mix it, and then use DMF solution to filter and wash the product three times.

[0053] 3) The product obtained in the previous step was placed in a vacuum oven at 130 °C and dried for 12 h to remove excess DMF. The dried product was then placed in a muffle furnace and heated to 700 °C at a rate of 5 °C / min, kept at that temperature for 6 h, and naturally cooled to room temperature before being taken out to complete the lanthanide modification.

[0054] Embodiment 4: 1) Dissolve 1.737 g of cerium nitrate hexahydrate, 1.732 g of lanthanum nitrate hexahydrate and 1.797 g of ytterbium nitrate pentahydrate in 20 ml of DMF solution and mix thoroughly to form a 0.2 mol / L uniform solution.

[0055] 2) Take 0.2 g of secondary particles of polycrystalline high-nickel NCM811 powder and dissolve it in 4 ml of the above-prepared solution, place it in a vacuum environment, and stir it at 80 °C for 8 h to fully mix. The subsequent product is filtered and washed repeatedly with DMF solution for 3 times.

[0056] 3) The product obtained in the previous step was placed in a vacuum oven at 130 °C and dried for 10 h to remove excess DMF. The dried product was then placed in a muffle furnace and heated to 650 °C at a rate of 5 °C / min, kept at that temperature for 6 h, and naturally cooled to room temperature before being taken out to complete the lanthanide modification.

[0057] Embodiment five: 1) Dissolve 1.737 g of cerium nitrate hexahydrate, 1.732 g of lanthanum nitrate hexahydrate and 1.797 g of ytterbium nitrate pentahydrate in 40 ml of DMF solution and mix thoroughly to form a 0.1 mol / L uniform solution.

[0058] 2) Take 0.2 g of secondary particles of polycrystalline high-nickel NCM523 powder and dissolve it in 4 ml of the above-prepared solution, place it in a vacuum environment, and stir it at 80 °C for 8 h to fully mix. The subsequent product is filtered and washed repeatedly with DMF solution for 3 times.

[0059] 3) The product obtained in the previous step was placed in a vacuum oven at 130 °C and dried for 10 h to remove excess DMF. The dried product was then placed in a muffle furnace and heated to 750 °C at a rate of 5 °C / min, kept at that temperature for 6 h, and naturally cooled to room temperature before being taken out to complete the lanthanide modification.

[0060] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A lanthanide-coated doped dual-modified positive electrode composite material, characterized in that: Form Q rich in oxygen vacancies on the surface of the cathode material of the lithium-ion battery 1-x-y M x N y O 1.9 lanthanide oxide coating layer, where 0 < x < 1, 0 < y < 1, Q, M, and N are a composition of one or more of La, Ce, Pr, Nd, Pm, Sm, Sc, Y, and Yb. The lanthanide elements in the oxygen vacancy lanthanide oxide coating layer are doped into the layered structure of the cathode material, and coherent nanoprecipitation phases are formed between the material layers to achieve double modification of surface coating and interlayer-like doping.

2. The lanthanide-coated doped dual-modified positive electrode composite material according to claim 1, characterized in that Q is Ce, M is La, and N is Yb.

3. The lanthanide-coated doped dual-modified positive electrode composite material according to claim 1, characterized in that: Where 0 <x<0.35,0<y<0.35。 4. The lanthanide-coated doped dual-modified positive electrode composite material according to any one of claims 1 to 3, wherein the surface forms a Q rich in oxygen vacancies. 1-x-y M x N y O 1.9 The stoichiometric ratio of the lanthanide elements in the lanthanide oxide is 1:1:1, and the coating layer thickness is 1-5 nm.

5. A method for preparing the lanthanide-coated doped dual-modified positive electrode composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Dissolving different lanthanide sources in a certain amount of N,N-dimethylformamide (DMF) according to a stoichiometric ratio to form a uniform solution; 2) A certain mass of original cathode material powder is dissolved in a certain amount of the above solution, placed in a vacuum environment and mixed evenly, and then the mixed product is washed multiple times with DMF solution; 3) Drying the product obtained in the previous step in a vacuum oven, and then sintering the dried product to obtain a modified positive electrode composite material.

6. The method according to claim 5, characterized in that: In the step 1), the lanthanide source in the step 1) is one or more of nitrates, acetates, sulfates and chlorides of lanthanide.

7. The method according to claim 5, wherein the concentration of the final mixed solution in step 2) is 0.1-1 mol / L.

8. The method according to claim 5, characterized in that: In the step 2), the original positive electrode material powder includes primary particles synthesized by the sol-gel method and secondary particles synthesized by the coprecipitation-solid phase method, the stirring temperature is 50-120° C., the time is 5-12 h; the DMF solution is repeatedly filtered and washed 3 times.

9. The method according to claim 5, characterized in that: In the step 3), the drying condition is drying at 120-140° C. for 12 h in a vacuum oven; the sintering condition is heating to 600-800° C. at a heating rate of 5° C. / min, keeping the temperature for 6-12 h, and naturally cooling to room temperature.

10. Use of the nanocomposite material according to claims 1-4 or the nanocomposite material prepared by the method according to claims 5-9 in batteries, wherein the batteries include lithium ion batteries, sodium ion batteries and potassium ion batteries.

Citation Information

Patent Citations

  • Composite high-voltage ternary positive electrode material as well as preparation method and application thereof

    CN116722118A

  • Cationic disordered lithium-rich spinel oxide, preparation method and application

    CN117996065A

  • Trace multi-element doped strontium cobalt-based perovskite electrode material, preparation method and application in reversible solid oxide battery

    CN118448653A

  • Lagao3 solid electrolyte fuel cell

    JP2001351646A

Cited By

  • Modified nickel cobalt lithium manganate positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery

    CN120767324A

  • High-stability lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN121662795A

  • A high-stability lithium-rich manganese-based positive electrode material, a preparation method and application thereof

    CN121662795B